Dampak Artificial Intelligence (Ai) Terhadap Pendidikan Di Indonesia - Waita, Badriello Chenny; Yiswi, Trivena Apriska; Kristiahadi , Ariella (Publikasi Indonesia, 2025)
Artificial Intelligence (AI) technology advancements have brought about profound transformations across various domains, including education. This study aims to critically examine the implementation of AI within multiple facets of the Indonesian education system, encompassing teaching methodologies, learning assessment, and administrative management. Employing a qualitative approach through a comprehensive literature review, this research integrates conceptual and empirical findings from reputable academic sources. The results of this study underscore the necessity of strengthening collaborative efforts among government entities, educational institutions, and the technology sector to foster an inclusive, adaptive, and sustainable digital transformation in education.